THE EFFECT OF ROA, FDR, AND NPF ON THE PROFIT-SHARING RATE FOR MUDHARABAH DEPOSIT IN BPRS, INDONESIA - Hurin 'In Pujiastutik; Agus Sumanto (Universitas Negeri Medan, 2020)
Until now, Islamic banking has grown very rapidly. This can be seen from the number of Islamic products that continue to grow and develop. One of them is mudharabah deposit. The profit-sharing rate that is characteristic of mudharabah deposits is the public's appeal to deposit their funds in banks, especially mudharabah deposit products. This study aims to determine the effect of financial ratios on the profit sharing rate of BPRS mudharabah deposits in Indonesia. The population used is the monthly financial reports of all BPRS in Indonesia from January 2012 to April 2018 in the form of time series data. The variables used in this study are Return on Assets (ROA), Financing to Deposit Ratio (FDR), and Non Performing Financing (NPF) as independent variables, and the profit sharing rate of mudharabah deposits from Bank Pembiayaan Rakyat Syariah (BPRS) as the dependent variable. Simultaneously, the variables ROA, FDR, and NPF together have a significant effect on the profit sharing of BPRS mudharabah deposits in Indonesia. Meanwhile, partially ROA has no significant effect on the profit sharing of BPRS mudharabah deposit in Indonesia. The FDR has a positive and significant effect on the profit sharing of the mudharabah deposits of Islamic rural banks in Indonesia. As well as NPF has a negative and significant effect on the profit sharing of mudharabah deposits in BPRS in Indonesia.